1998
DOI: 10.1038/sj.hdy.6882980
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic correlations in plants: a botanical test of Cheverud's conjecture

Abstract: A survey of the agricultural and evolutionary literature was undertaken to determine the extent to which phenotypic correlations reflect their genetic counterparts in plants. More than 4000 phenotypic and genetic correlations representing 27 different plant species and over 40 years of research were analysed. In 74 per cent of the comparisons, the arrangement of elements of different magnitudes in genetic and phenotypic correlation matrices was more similar than would be expected by chance alone. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 9 publications
6
51
1
Order By: Relevance
“…Nevertheless, most of these correlations vanished for the populations studied separately, suggesting that floral-size traits are not actually coupled with vegetative traits in E. mediohispanicum. This finding agrees with most studies, which have shown that genetic and phenotypic correlations between floral and vegetative character suites are low and mostly statistically nonsignificant (Conner and Via 1993;Conner and Sterling 1996;Waitt and Levin 1998;Armbruster et al 1999;Worley and Barrett 2000;Juenger et al 2005;Ashman and Majetic 2006).…”
Section: Genetic Correlations Among Traitssupporting
confidence: 93%
“…Nevertheless, most of these correlations vanished for the populations studied separately, suggesting that floral-size traits are not actually coupled with vegetative traits in E. mediohispanicum. This finding agrees with most studies, which have shown that genetic and phenotypic correlations between floral and vegetative character suites are low and mostly statistically nonsignificant (Conner and Via 1993;Conner and Sterling 1996;Waitt and Levin 1998;Armbruster et al 1999;Worley and Barrett 2000;Juenger et al 2005;Ashman and Majetic 2006).…”
Section: Genetic Correlations Among Traitssupporting
confidence: 93%
“…Therefore, although we expect pollination to affect trait means, we do not expect it to influence the genetic correlations among traits. Most of the phenotypic correlations not involving the flower number and size trade-off were in the same direction as genetic correlations but were somewhat weaker, which follows the predictions and observations of Cheverud (1988; see also Waitt and Levin 1998). However, phenotypic correlations between stem mass and flower number were greater than genetic correlations in both males and females.…”
Section: Highersupporting
confidence: 82%
“…Phenotypic correlations can only be used to assess whether evolutionary responses are constrained if it is reasonable to assume that phenotypic correlations are representative of underlying genetic correlations (Cheverud 1988;Roff 1995;Waitt and Levin 1998). We estimated genetic correlations for the same 36 pairwise comparisons of traits (Table 1): the correspondence between the genetic and phenotypic correlations was quite good (r Ï­ 0.722, n Ï­ 36, P Ïœ 0.0001).…”
Section: Relationships Between Traitsmentioning
confidence: 99%